Improving the cam profile of the spring operating mechanism of vacuum circuit breaker based on energy matching. Issue 1 (July 2021) - Li, Fuqiang; Wang, Shufen; Li, Yuguang; Sun, Zhenzhen
Abstract: High-voltage circuit breakers are important protection and control equipment in power systems. In order to understand the mechanical characteristics of vacuum circuit breaker, the mathematical relationship between the released energy of closing spring, the stored energy of opening spring and overtravel spring and the rotation angle of output crank arm is studied. The characteristic curve between the released energy of closing spring and the rotation angle of output crank arm and the characteristic curve between the stored energy of opening spring and overtravel spring and the rotation angle of output crank arm are drawn by MATLAB. In order to improve the matching of energy release and energy storage characteristic curves, a method of improving cam profile is proposed. The dynamics simulation model of spring operating mechanism of high voltage circuit breaker is established and the original cam and adjusted cam are imported into the dynamics simulation model of mechanism. The simulation results show that the adjusted cam improves the closing speed of vacuum circuit breaker. This helps to reduce the stress on the parts of the vacuum circuit breaker and increase the service life of the vacuum circuit breaker.